Biodiversity Literacy Skills in Problem-Based Science Lectures: A Grounded Theory Research - Hiola, Zohra Waty; Katili, Abubakar Sidik; Husain, Ilyas H. (FKIP Universitas Lampung, 2023)
The aims of this study to describe the students biodiversity literacy skills in natural science lectures. The data research from the observation and the test scores. Biodiversity literacy skills indicators were established. Analysis of data using qualitative descriptive methods. The results showed the biodiversity literacy skills are within medium, high and very high criteria. Based on indicators of biodiversity literacy skills, it is in the criteria of being able to define biodiversity and its use, being able to distinguish biodiversity at the gene, species, ecosystem level, and being able to construct solutions to biodiversity problems. This biodiversity literacy skill can encourage the character of concern for biodiversity decline so that students are able to come up with solutions to existing biodiversity problems.Keywords: biodiversity literacy skills, science lectures, grounded theory approach.DOI: http://dx.doi.org/10.23960/jpmipa/v24i1.pp50-58